Assessment, teaching and learning practicesin physical education during the pandemic: expectations and realities (Educação e Pesquisa, 2023)
The constraints of the pandemic challenged the characteristics of proximity and physical contact of Physical Education (PE), which may have led to the reinvention of the subject. However, in the Portuguese context, we have little knowledge about the extent of these constraints, particularly in the relationship of interdependence between the practices of teaching, assessment, and learning. The reconfiguration of these practices resulted from the expectations of upstream entities, which affected the PE teachers’ actions. However, little is known about the relationship between those recommendations and the school’s reality, compared to what was foreseen in the curriculum for normal conditions. This knowledge is relevant for the post-pandemic intervention and educational intentionality. In order to fill this empty field, we implemented an investigation to access the practices of teaching, assessment and learning recomended by the PE representative entities and adopted by teachers, depending on the pandemic period. It falls within the interpretative paradigm, with a qualitative approach in the modality of basic interpretative study. Data was collected by documental analysis and interviews with semi-structured script and treated by content analysis. The results suggest that the teaching practices were disaggregated and lost reciprocity; and that the expectations of the entities were misaligned with the needs of teachers in the context. Thus, PE, sensitive to the pandemic situation, became desensitized, due to the loss of relationships between teaching, assessment, and learning. Also, PE became deprojected because it lost elements of its curricular project and its educational projection. These results may contribute to consolidate the marginalization of PE and advises the reconnection between teaching, assessment, and learning.